Relating students' units coordinating and calculus readiness. Issue 3 (3rd July 2021) - Boyce, Steven; Grabhorn, Jeffrey A.; Byerley, Cameron
ABSTRACT: Adolescent and children's concepts of multiplication and fractions have been linked to differences in the number of levels of units they coordinate. In this paper, we discuss relationships between adult students' conceptual structures for coordinating units and their pre-calculus understandings. We conducted interviews and calculus readiness assessments with 27 introductory calculus students at a public university in the United States. Results indicate that students assimilating multiplicative situations with three levels of units performed significantly better on calculus readiness assessments than students assimilating multiplicative situations with fewer than three levels of units. We discuss implications for instruction.